Corneal Ulcer Impending Perforation et causa Corpus Alienum - Fanda Aviesta Minhalina; Niken Indah Noerdiyani (Vision Science and Eye Health Journal, 2023)
Introduction: The cornea is a transparent, avascular tissue that serves as a structural barrier and protects the eye from infection. A corneal ulcer is an inflammatory or, more dangerously, infective disorder involving abnormalities of the cornea’s epithelial layer or stroma. Corneal ulcers can develop due to contact lenses, trauma, adnexal illnesses, or ocular surface abnormalities. Despite aggressive nonsurgical therapies, corneal perforation frequently occurs in the event of resistant corneal ulcers. The anatomic integrity of the eyeball must be preserved through urgent surgical intervention to avoid potentially fatal consequences such as endophthalmitis, subsequent glaucoma, perforation, or corneal scarring. Case Presentation: A-11-year-old male child was taken to Community Eye Hospital, East Java due to a corneal ulcer. He complained of pain and redness right after he played with bamboo two weeks ago. The patient had been previously treated in other hospitals; however, there was a worsening of symptoms rather than improvement. Clinical examination of oculus sinister revealed a conjunctival injection, episcleral injection, corpus alienum (bamboo) sized 50 mm, an ulcer in the central cornea sized 3 x 2 mm irregular, shallow anterior chamber, impending perforation in the central cornea with a diameter of 2 mm. Thus, there had shown impending perforation, and the patient had to undergo surgery, of amniotic graft and antibiotic injection immediately to avoid perforation. Conclusions: A perforation, an ophthalmological emergency requiring surgery, can result from corneal ulceration, a medical emergency. The primary objectives of the procedure are to restore the eye’s anatomical integrity and to reduce problems as much as feasible.